Dance as a contemplative practice: The space of distinction and union - Hellsten, Laura (Approaching religion, 2021)
This article analyses ethnographic material gathered in Sweden amongst dancers in the Church of Sweden. With the help of the writings of Sarah Coakley and Simone Weil I explore if, and how, dancing could be considered a contemplative practice in the Christian traditions of the Latin West.